Bentuk, Makna, dan Fungsi Sastra Lisan Pujian di Kelurahan Bugul Lor Kota Pasuruan - Mahmudah Mahmudah (Jurnal Simki Pedagogia, 2021)
Study in this research is the form, meaning, and function of the oral literature of praise that is sung after the call to prayer and before performing the prayers. The purpose of the study entitled "Form, Meaning, and Function of Praise Oral Literature in Bugul Lor Village, Pasuruan City" describe the form, meaning, and function of praise oral literature in Bugul Lor Village, Pasuruan City. This research is expected to increase knowledge about the form, meaning, and function of praise before prayer, about culture, as well as preserving culture and traditions. The method used is descriptive qualitative. The research data is written data in the form of praise poems. The source of research data is in the form of poetry lyrics sung in mosques and prayer rooms in Bugul Lor Village, Pasuruan City. The collection is done by observing and taking notes. The results of the discussion can be concluded that the oral literature of pujian is in the form of poetry consisting of 2 to 4 stanzas consisting of 4 lines, in 1 line consisting of 8 to 16 syllables. Not all rhymes are a-a-a-a, there are some verses where the rhyme is free, or the rhyme is like a rhyme (a-b-a-b). All lines contain content. The meaning of praise consists of semantic and semiotic meanings. The function of praise oral literature is as a collective wishful thinking, as well as having an educational function.